2007
DOI: 10.3748/wjg.v13.i18.2622
|View full text |Cite
|
Sign up to set email alerts
|

Expression level of beta-catenin is associated with prognosis of esophageal carcinoma

Abstract: AIM:To examine the association of beta-catenin with the clinicopathologic features and prognosis of esophageal squamous cell carcinoma (ESCC).METHODS: Beta-catenin mRNA expression level in 40 ESCC patients (28 males and 12 females, age range 38-82 years, median 60 years) was analyzed by realtime PCR. Beta-catenin mRNA expression levels in tumor cells were categorized as weaker (level 1) or equal to or stronger (level 2) than those in endothelial cells. We examined the correlation between the beta-catenin expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…So, it is important to explore what role Wnt=b-catenin plays in ESCC. A previous study had found that b-catenin mRNA expression was obviously abnormal in early ESCC and overexpression was implicated in poor prognosis of ESCC patients ( Ji et al, 2007). Without a doubt, the present results proved it once again.…”
Section: Discussionsupporting
confidence: 81%
“…So, it is important to explore what role Wnt=b-catenin plays in ESCC. A previous study had found that b-catenin mRNA expression was obviously abnormal in early ESCC and overexpression was implicated in poor prognosis of ESCC patients ( Ji et al, 2007). Without a doubt, the present results proved it once again.…”
Section: Discussionsupporting
confidence: 81%
“…The Wnt signaling pathway may be activated through the accumulation and/or altered localization of β-catenin. Thereafter, β-catenin forms a complex with the TCF/LEF family of transcription factors, resulting in the activation of growth-controlling genes ( 14 17 ). The role of β-catenin in human carcinomas has been extensively studied ( 15 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports indicate that esophageal squamous cell carcinoma (ESCC) has abnormal nuclear accumulation of β-catenin accompanied with increased cyclin D1 expression 135 . β-catenin mRNA expression has appeared a new prognostic marker for ESCC 136 . Overexpression of β-catenin and its target proteins is commonly observed in human Eca109 tumor xenografts.…”
Section: Targeting Cancer Cells By Regulating Multiple Signaling Pmentioning
confidence: 99%